(untitled) (Bangladesh Medical Journal, 2014)
Adverse drug Reactions (ADRs) is a global problem of major health concern. Spontaneous reporting of ADRs is the cornerstone of pharmacovigilance. However, underreporting is a huge problem due to lack of reporting culture among medical practitioners. This observational descriptive study was done with the aim to find out the response of reporting adverse drug reactions among medical practitioners and to describe pattern of adverse drug reactions during their practice. Self administered ADR reporting form was distributed to one teaching hospital and ten (10) medical practitioners during the period of December 2009 to December 2010. Total 85 report forms were supplied and response rate was 35% (30185). Among 30 reported cases 16 (53%) were due to antimicrobial, agents and other 14 (47%) cases were due to NSA!Ds, anti psychotics, antidiabetic, antithyroidal, antiepileptics, muscle relaxants and anesthetic agents. 15 cases (50%) need hospitalization for AD Rs, 04 (13%) cases suffer > 1 month and one (3%) case was fatal. 20 cases (67%) express hypersensitivity reaction of various grade and rest reports septicemia, fever, palpitation, tachycardia, dryness of mouth, abdominal pain, swelling of limb, heart burn, restlessness, anorexia, apnoea during anesthesia. All reaction is very important and successfully managed by physicians but reporting not done may be due to lack of awareness. So, steps should be taken at different levels to increase the awareness of reporting adverse drug reactions among medical practitioners and we should strengthen pharmacovigilance in our country DOI: http://dx.doi.org/10.3329/bmj.v40i2.18498 Bangladesh Medical Journal 2011 Vol.40(2): 13-18